Deciphering the crosstalk of immune dysregulation between COVID-19 and idiopathic inflammatory myopathy - Zhang, Zhao; Tao, Weidong; Cheng, Debin; Qin, Marong; Fu, Jun; Liu, Dong (Frontiers in Immunology, 2023)
The COVID-19 pandemic seriously threatens the public health worldwide. Growing evidence reveals that there are certain links between COVID-19 and autoimmune diseases, in particular, COVID-19 and idiopathic inflammatory myopathies (IIM) have been observed to be comorbid in clinical. Hence, this study aimed to elucidate the molecular mechanism between COVID-19 and IIM from a genomic perspective.We obtained transcriptome data of COVID-19 and IIM patients separately from the GEO database and identified common differentially expressed genes (DEGs) by intersection. Then, we performed functional enrichment analysis, PPI analysis, machine learning, gene expression regulatory network analysis, and immune infiltration analysis on co-expressed genes.2 This is a provisional file, not the final typeset article Results: A total of 91 common genes were identified between COVID-19 and IIM. Functional enrichment revealed that these genes were involved mainly in immune dysregulation, response to external stimulus and MAPK signaling pathways. The MCODE algorithm recognized two densely linked Cluster in the common gene, which were related to inflammatory factors and interferon signaling, respectively. Subsequently, three key genes (CDKN1A, IFI27, STAB1) were screened by machine learning for predicting the occurrence of COVID-19 related IIM. These key genes exhibit excellent diagnostic performance in both the training cohort and the validation cohort. Moreover, we created TF-gene and miRNA-gene networks to reveal the regulation of key genes. Finally, we estimated the relationship between key genes and immune cell infiltration, of which IFI27 was positively associated with macrophage M1.Our work revealed the common molecular mechanisms, core genes, potential targets and therapeutic approach between COVID-19 and IIM from a genomic perspective. This provided new thoughts for the diagnosis and treatment of COVID-19 related IIM in the future.